Studies on the shootborer Hypsipyla grandella (Zeller) (Lepidoptera Pyralidae). II. Host preference of the larva - Grijpma, P.; Gara, R.I. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
In a previous study (Turrialba 20(2).85-93), it was reported that adult Hypsipyla grandella Zeller had a preference for American Meliaceae. However, very little is known about the stimuli that induce H. grandella larvae to feed and develop appropriately.